Epigenetic mechanisms of drug resistance in acute myeloid leukemia: advances in small-molecule targeted therapy - Tang, Jialing; Ye, Xibo; Xu, Zhangyang; Min, Tianjiao; Tian, Zherun; Ma, Li; He, Ying; Jiang, Beier (Frontiers in Pharmacology, 2025)
Acute myeloid leukemia (AML) remains a formidable therapeutic challenge, with high relapse rates rooted not only in genetic heterogeneity, but also in dynamic and reversible epigenetic dysregulation that drive resistance to conventional and targeted small-molecule therapies. Although small-molecule inhibitors targeting epigenetic regulators have demonstrated preclinical efficacy and initial clinical activity, therapeutic gains are often limited by transient responses, intra- and inter-patient heterogeneity, and an incomplete understanding of predictive biomarkers. Besides, clinical outcomes have often been less robust than preclinical data suggested, partly due to the complexity of AMLs genetic and epigenetic heterogeneity, the limitations of model systems, and intrinsic resistance mechanisms. Combination approaches, such as pairing epigenetic agents with chemotherapy, immunotherapy, or other targeted drugs are under investigation. However, clinical efficacy remains inconsistent and requires a mechanistic rationale to avoid antagonism. To move forward, it is essential to delineate specific epigenetic dependencies in resistance-prone AML subtypes, design rational, biomarker-guided combination regimens, and enhance specificity and pharmacodynamic profiles of epigenetic inhibitors. Such an integrated strategy holds promise for elevating the effectiveness of epigenetic therapies in AML. Continued research is essential to refine epigenetic-based precision medicine and ultimately improve patient outcomes.